2021
DOI: 10.1002/jcp.30563
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid stimulating hormone aggravates diabetic retinopathy through the mitochondrial apoptotic pathway

Abstract: Diabetic retinopathy (DR) is a common complication of diabetes mellitus. High glucose‐induced mitochondrial apoptosis is involved in the loss of retinal pericytes (PCs), which is considered to be a predominant pathologic change of diabetic retinopathy (DR). A high thyroid stimulating hormone (TSH) serum level is associated with an increased prevalence of DR in diabetic patients. Here, we investigated whether TSH regulated glucose‐induced PCs loss through TSH‐receptor (TSHR)‐dependent mitochondrial apoptosis. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…For example, hyperglycemia-induced ER stress may lead to apoptosis and pericytes loss ( Lai et al, 2017 ). High levels of thyroid stimulating hormone may facilitate the effect of high glucose-induced pericyte loss through thyroid stimulating hormone -receptor -dependent mitochondrial apoptosis in retinal pericytes ( Lin et al, 2021 ). DNA methyltransferase-1 can prevent the overexpression of peroxisome proliferator-activated receptor α by mediating its methylation to increase apoptotic cells and ROS in pericytes ( Zhu Y. et al, 2021 ).…”
Section: Involved Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, hyperglycemia-induced ER stress may lead to apoptosis and pericytes loss ( Lai et al, 2017 ). High levels of thyroid stimulating hormone may facilitate the effect of high glucose-induced pericyte loss through thyroid stimulating hormone -receptor -dependent mitochondrial apoptosis in retinal pericytes ( Lin et al, 2021 ). DNA methyltransferase-1 can prevent the overexpression of peroxisome proliferator-activated receptor α by mediating its methylation to increase apoptotic cells and ROS in pericytes ( Zhu Y. et al, 2021 ).…”
Section: Involved Cellsmentioning
confidence: 99%
“…The metabolic disturbances induced by DR are mainly related to metabolism of glycolysis, polyols, tricarboxylic acid, amino acids, the urea cycle, and lipids ( Xuan et al, 2020 ). Several observational studies have shown that dyslipidemia, mitochondrial apoptosis, and oxidative stress may be the predominant pathological changes of DR ( Miller et al, 2020 ; Fort et al, 2021 ; Lin et al, 2021 ; Rao et al, 2021 ). Vascular endothelial growth factor (VEGF), HbA1c, low-density lipoprotein cholesterol, myeloperoxidase, and advanced glycation end products (AGEs) are pathogenic factors of DR.…”
Section: Introductionmentioning
confidence: 99%
“…Abnormally high TSH expression can accelerate oxidative stress, induce vascular endothelial cell damage, and alter local hemodynamics in T2DM patients. 17 These pathological changes can aggravate damage to endothelial cells in the fundus, thicken the basement membrane, and block capillaries, thereby causing visual impairment in T2DM patients. A cross-sectional study found that high TSH levels are an independent risk factor for diabetic macular edema in T2DM patients.…”
Section: Discussionmentioning
confidence: 99%
“…The potential mechanism underlying the effects of TSH on the development of DR has been investigated in several studies. Lin et al 30 . detected functional TSH receptors in retinal pericytes, which may facilitate the effect of high TSH on high glucose‐induced PC loss through TSH‐receptor‐dependent mitochondrial apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…The potential mechanism underlying the effects of TSH on the development of DR has been investigated in several studies. Lin et al 30 detected functional TSH receptors in retinal pericytes, which may facilitate the effect of high TSH on high glucose-induced PC loss through TSH-receptor-dependent mitochondrial apoptosis. Furthermore, high TSH levels have been reported to be associated with early retinal changes, including retinal arteriolar narrowing 31 and opsin expression changes.…”
Section: Since the Landmark Diabetes Control And Complications Trialmentioning
confidence: 99%